MIXED METHODS IN AUDIENCE RESEARCH AS A RESOURCE FOR THE ANALYTICAL CAPABILITIES AND RESILIENCE OF BUSINESS AND CIVIL SOCIETY ORGANISATIONS - Shkurov, Yevhen; Severynchyk, Oleksii; Bakhanov, Oleksii (Current Problems of Sustainable Development, 2026)
The article substantiates the role of mixed methods in strengthening the analytical capabilities and resilience of business and civil society organisations in wartime and digitally fragmented environments. The study is relevant because war, migration, limited access to some audiences, digital inequality, online data, artificial intelligence tools and sensitive topics complicate the collection, verification and interpretation of audience data. The aim of the article is to justify mixed methods as a resource for analytical capabilities and to develop a framework for their integrated use in organisational decision-making under uncertainty. The contribution of the article lies in bringing together three applied research optics – marketing, advertising and communication, and sociological – into a single logic for supporting managerial and communication decisions. The scientific novelty consists in interpreting mixed methods as a means of working with fragmented data, combining scale with context, examining contradictions between sources, and accounting for online data quality, ethical risks and the limits of evidence. The article shows that this logic supports business decisions concerning segmentation, products, services, pricing, advertising creative, media channels and brand trust. For civil society organisations, it is relevant to needs assessment, programme evaluation, work with internally displaced persons, veterans, young people and vulnerable groups, advocacy campaigns and donor reporting. The study concludes that quantitative methods provide scale and comparability, qualitative methods reveal motives, barriers, audience language and lived context, while advertising and communication research helps assess message perception, emotional response, trust and the ethical acceptability of communication. The proposed framework may be used by research agencies, enterprises, civil society organisations, universities and professional associations for planning research in wartime and post-war settings.